Expert MySQL - Belli, Charles A. (2012)
MySQL has been identified as the world’s most popular open source database and the fastestgrowing database system in the industry. MySQL AB is reporting over 8 million active installations and nearly 50,000 downloads per day. MySQL is rapidly becoming the database system of choice for system integrators. According to an article in the SD Times, MySQL is now the number three “Top Deployed Database” in a recent survey of over 900 readers (www.mysql.com/why-mysql/ marketshare/). This book presents some advanced database system topics, examines the MySQL architecture, and provides an expert’s workbook for examining, integrating, and modifying the MySQL source code for use in enterprise environments. The book provides insight into how to modify the MySQL system to meet the unique needs of system integrators and educators alike.